The advantages gained by the use of modern materials in the post operative casting procedure for foot and ankle surgery - Dean, B.J.F.; Hinsley, D.E.; Mackay, B.; Rice, P.S.; Cooke, P.H.; Sharp, R.J. (Foot and ankle surgery, 2009)
In June 2006, the post operative plaster immobilisation protocol for patients undergoing hindfoot and ankle surgery, at our institution, changed from multiple plaster changes to the immediate application of a definitive removable and reusable split synthetic cast. This study aims to assess the savings to the hospital and patient, following this change in practice. A retrospective analysis of plaster room records from June 2005 to June 2007 was performed. The difference in cost to the hospital of the two different post operative journeys was then calculated. Two-hundred and twenty-two patients from 2005 to 2006 were managed at a total cost of €97,125. From 2006 to 2007, 203 patients were managed with the new technique at a total cost of €37,860. The net saving to the hospital of this change in practice was €251 per patient and €50,953 in total, while 203 patient visits and costs associated therewith were also saved. This study demonstrates how small changes in local practice can result in significant financial and temporal savings for hospitals and patients.